Penerapan Strategi Pembelajaran Inkuiri dalam Mata Pelajaran IPA Kelas VII di MTsN 3 Kerinci - Anita, Desvia; Bentri, Alwen (Jurnal Family Education, 2023)
This study aims to evaluate the application of inquiry learning strategies in class VII natural science subjects at MTsN 3 Kerinci. The research method used is classroom action research conducted in several cycles. Participants in this study were students of class VII at MTsN 3 Kerinci. In this study, the teacher implemented an inquiry learning strategy that involved students actively in exploring and discovering knowledge through asking questions, seeking information, and conducting experiments. During the study, data was collected through classroom observations, interviews with teachers, and written tests to measure students' understanding of science concepts. The results showed that the application of inquiry learning strategies in class VII science subjects at MTsN 3 Kerinci had a positive impact on the learning process and students' understanding. Students are actively engaged in exploration and discussion, enhancing their critical thinking skills and scientific skills. In addition, the test results showed a significant increase in students' understanding of science concepts after implementing the inquiry strategy. This research concludes that the application of inquiry learning strategies can be an effective approach in enhancing science learning at the MTs level. It is suggested that teachers should more actively adopt this strategy and provide the necessary support to facilitate student inquiry in their learning